Criminal Act of Document Forgery Under Article 263 Paragraphs (1) and (2) of the Indonesian Penal Code - Tedy Subrata; Suandi Suandi; Markuat Markuat; Salmah Salmah; Turija Turija; Chairul Aman (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Document forgery is a criminal offense that frequently occurs in society, despite being clearly regulated under Article 263 Paragraphs (1) and (2) of the Indonesian Penal Code (KUHP). This community service activity, conducted in Bantarpanjang Village, Tigaraksa District, Tangerang Regency, aims to raise public legal awareness regarding document forgery crimes. Through legal education sessions, the community was informed about the elements of documented forgery offenses, various forms of forgery, and the associated legal consequences, including imprisonment of up to six years. The program also emphasizes the importance of verifying the authenticity of documents used in legal and social transactions. The results showed high enthusiasm and participation from the community, along with an increase in their understanding of the importance of valid legal documents. Comprehensive evaluations were carried out to measure the effectiveness, sustainability, and impact of the program in enhancing community legal awareness.